2020
DOI: 10.1161/jaha.119.013403
|View full text |Cite
|
Sign up to set email alerts
|

Total Sitting Time and Sitting Pattern in Postmenopausal Women Differ by Hispanic Ethnicity and are Associated With Cardiometabolic Risk Biomarkers

Abstract: Background Sedentary behavior is pervasive, especially in older adults, and is associated with cardiometabolic disease and mortality. Relationships between cardiometabolic biomarkers and sitting time are unexplored in older women, as are possible ethnic differences. Methods and Results Ethnic differences in sitting behavior and associations with cardiometabolic risk were explored in overweight/obese postmenopausal women (n=518; mean± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…Many older adults find it challenging to engage in health-enhancing physical activity (PA) and can spend up to 11 hours a day sitting [ 1 ]. Greater amounts of sedentary time, including time spent sitting and lack of PA, are associated with an increased risk of type 2 diabetes; all-cause mortality; cardiovascular disease; higher insulin; hypertension; and, specifically in older adults, poorer physical functioning [ 2 - 11 ]. Older women, in particular, are at an increased risk of chronic diseases and disabilities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many older adults find it challenging to engage in health-enhancing physical activity (PA) and can spend up to 11 hours a day sitting [ 1 ]. Greater amounts of sedentary time, including time spent sitting and lack of PA, are associated with an increased risk of type 2 diabetes; all-cause mortality; cardiovascular disease; higher insulin; hypertension; and, specifically in older adults, poorer physical functioning [ 2 - 11 ]. Older women, in particular, are at an increased risk of chronic diseases and disabilities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have developed new analytic approaches for accelerometer data in an effort to not just measure total accumulation of PA/SB time but to detect patterns in the data. Several studies have investigated patterns based on lengths of uninterrupted intervals ("bouts") and/or degree of fragmentation of PA/SB [15,22,[51][52][53][54][55][56][57]. More relevant to the current investigation, studies have also described variations in the timing of sedentary time and PA time accumulation with respect to hour of the day and/or day of the week, including differences in timing by sociodemographic factors [23,28,[58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies used selfreported measurements of SB, which can be unreliable or inaccurate, especially in older age groups [17][18][19]. Accelerometer data are subject to less measurement error, and analyses of these data have revealed stronger associations between SB and health than were previously observed using self-reports [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Activity measurement and sitting pattern classification. Activity measurement and sitting pattern characterization were described previously 7 . Briefly, all participants from the three studies wore an accelerometer (ActiGraph GT3X +) on their right hip for at least 4 days and up to 14 days, depending on the parent clinical study.…”
Section: Methodsmentioning
confidence: 99%
“…Sitting is a non-movement posture form of sedentary behavior 4 . Using device-based measures of sitting behavior, we recently showed that longer total sitting time and mean sitting bout duration (i.e., sitting pattern) were associated with cardiometabolic and cancer risk biomarkers among 518 overweight and obese postmenopausal women 7 . In this population, the women had a mean (SD) daily sitting time of 9.1 (1.6) hours and a mean (SD) sitting bout duration of 39.2 (15.5) minutes.…”
mentioning
confidence: 99%